A microhap panel for kinship analysis through massively parallel sequencing technology. Issue 3 (19th December 2019) - Qu, Ning; Lin, Shaobin; Gao, Yu; Liang, Hao; Zhao, Hu; Ou, Xueling
Abstract: It is widely recognized that microhaps are powerful markers for different forensic purposes, mainly due to their advantages of both short tandem repeats and single nucleotide polymorphisms, including multiple alleles, low mutation rate, and absence of stutter peaks. In the present study, a panel of 60 microhap loci was developed and utilized in forensic kinship analysis as a preliminary study. Genotyping of microhap was performed by massively parallel sequencing and haplotypes were directly achieved from sequence reads of 73 samples from Chinese Han population. We observed that 49 out of 60 loci have effective number of alleles greater than 3.0 and 10 out of 60 have values above 4.0, with an average value of 3.5598. The heterozygosity values were in a range from 0.5840 to 0.8546 with an average of 0.7268 and the cumulative power of exclusion value of the 60 loci is equal to 1–4.78 × 10 −18 . Moreover, we demonstrated the applicability of this method by different relationship inference problems, including identification of single parent‐offspring, full‐sibling, and second‐degree relative. The results indicated that the assembled microhap panel provided more power for relationship inference, than commonly used short tandem repeats or single nucleotide polymorphism system.